Directed Consumer-Generated Content (DCGC) for Social Media Marketing: Analyzing Performance Metrics from a Field Experiment in the Publishing Industry - Eleni Ntousi; Chris Lazaris; Pavlina Katiaj; Anastasios Koukopoulos (Systems)
This study examines the efficacy of a novel form of consumer-generated content (CGC) digital advertising, termed “directed” consumer-generated content (DCGC), in comparison to traditional brand-created social media advertisements. The analysis focuses on performance metrics and return on ad spend (ROAS). Data were gathered from social media campaigns incorporating both DCGC and non-CGC through a field experiment, followed by a rigorous statistical analysis to identify the most effective advertising strategies. Findings indicate that DCGC typically results in significantly higher conversion rates, increased conversions, and superior ROAS. Overall, DCGC advertisements demonstrate enhanced performance relative to non-CGC campaigns, suggesting that they represent a more strategic allocation of a brand’s marketing resources, particularly when the primary objective is to drive sales and achieve elevated conversion rates. This research contributes to the academic discourse and practical implementation of social media advertising by highlighting the advantages of DCGC as a cost-effective and efficient advertising approach for brands.